CAREER PERSPECTIVE OF HIGH SCHOOL STUDENTS: STUDY OF ENGLISH EXPERIENCE FOR IMPLEMENTATION IN UKRAINE - Voronina, Hanna (PEOPLE: International Journal of Social Sciences, 2018)
The paper analyses the different scholarly views on conceptual definition of “career perspective” and highlights innovative techniques of career planning at high school. The research focuses on the Ukrainian and English resources devoted to improving careers education. The main objective of the study is to research theoretical conceptual foundations of the principles, organizational and pedagogical tools for the development of career perspective of high school students in England. Other supportive goals of the study are to analyze and generalize the forms and methods of teaching and learning, which positively influence the development of career perspective of high school students in England. The methodological concept reflects the relationship and interaction of different approaches to general scientific and empirical methodology to the study of the educational process of high schools in England. The theoretical concept determines the system of conceptual and categorical apparatus of the research which relates to careers education as an effective pedagogical phenomenon. The concepts of “perspective” and “career perspective” are determined and specified, the effective methods of career perspective development of high school students in England are considered. The scholarly originality of the results is that holistic approach to theoretical aspects of career perspective of high school students in England is introduced with the view to further elaborating recommendations for implementing constructive ideas of the English experience in Ukraine in the sphere under research.